Implementasi Budaya Sekolah Dalam Membentuk Karakter Peserta Didik - Nurfatimah Nurfatimah; Sitti Habibah; Sumarlin Mus (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
The purpose of this study is to determine the implementation of school culture in shaping the character of students related to religion, nationalism, independence, mutual assistance, and integrity. This research approach is qualitative with a descriptive type of research. Data collection techniques include observation, interviews, and documentation. Data analysis techniques use data collection, data reduction, data presentation, conclusion drawing. Checking the validity of data using triangulation techniques. The results showed that: 1) Religious character, applied through routine and spontaneous habituation including dhuha prayer every Friday, reading prayers before and after learning, ablution practice, memorizing short surahs, and memorizing asmaul husna. 2) Nationalism character, applied through routine habituation including ceremonial exercises every Saturday, scouts every month. Then in class, namely memorizing the name of the hero, memorizing the youth oath, proclamation where this habituation is integrated into subjects based on the learning theme, and before entering the class doing a line of marching while memorizing student promises. 3) The character of Self-Reliance, applied through routine, spontaneous, and exemplary cleaning which includes cleaning outside and inside the classroom, reading, drawing, doing assignments or homework, lining up, preparing to start lessons, preparing shoes and storing on shoe racks. 4) The character of Gotong Royong, through routine, spontaneous, and exemplary habituation which includes service work every Friday, mutual help, and a scheduled class picket schedule every day. 5) Integrity character, applied through routine habituation and example, which includes obeying the rules that apply in schools.